“Subtype-precise” therapy leads diagnostic and therapeutic innovations: a new pattern for precision treatment of breast cancer - ZHANG Siwei, MA Ding, JIANG Yizhou, SHAO Zhimin (Zhongguo aizheng zazhi)
Breast cancer is the most common malignant tumor among women worldwide, with incidence rates rising annually. The treatment of breast cancer has undergone significant transformations, evolving from an initial reliance on a single surgical approach to the incorporation of systemic therapy, and more recently, to subtype-specific therapy. Clinically, breast cancer is classified into luminal, HER2-positive, and triple-negative breast cancer (TNBC) based on the expression of hormone receptor (HR) and human epidermal growth factor receptor 2 (HER2), with corresponding treatments including endocrine therapy, anti-HER2 targeted therapy, and chemotherapy. However, the current subtype-based treatment strategies lack personalization, with approximately 30% of patients still facing resistance and relapse. While the overall survival rate of patients with HER2-positive breast cancer has been steadily increasing, significant survival improvements have not been observed in patients with triple-negative and luminal breast cancer. To overcome the clinical bottleneck of “incomplete classification and imprecise treatment”, the concept of “subtype-precise” therapy has emerged. This innovative approach involves further subclassification of existing subtypes to identify specific targets for precision treatment, characterized by broad population coverage and high specificity. Over the past decade, the multidisciplinary team at Fudan University Shanghai Cancer Center has established a comprehensive molecular portrait of Chinese Breast Cancer Genome Atlas (CBCGA). They deeply analyzed the molecular characteristics of TNBC, leading to the development of a “Fudan subtype” closely related to clinical outcomes: luminal androgen receptor subtype (LAR), which can be targeted with anti-HER2 and CDK4/6 inhibitors; the immunomodulatory subtype (IM), suitable for immunotherapy; basal-like immune-suppressed subtype (BLIS), which can be treated with platinum-based drugs or poly (ADP-ribose) polymerase (PARP) inhibitors; and mesenchymal-like subtype (MES), which can be treated with anti-cancer stem cell and anti-angiogenic therapies. The team then extended the concept of “subtype-precise” to luminal breast cancer, the subtype with the largest number, the highest proportion and the risk of recurrence for decades. They divided it into four molecular subtypes and proposing corresponding precision treatment strategies: canonical luminal subtype (SNF1), sensitive to endocrine therapy; immunogenic subtype (SNF2), amenable to immunotherapy; proliferative subtype (SNF3), treatable by CDK4/6 inhibitors; and receptor tyrosine kinase-driven subtype (SNF4), targetable with tyrosine kinase inhibitors. The team is currently conducting phase Ⅲ randomized controlled trials to further validate the “subtype-precise” therapy and promote the “subtype-precise” Fudan experience to enhance overall breast cancer treatment efficacy. Looking forward, the integration of emerging diagnostic tools, such as artificial intelligence, coupled with the continuous update of subtype-specific targets and targeted therapies, is expected to further refine and expand “subtype-precise” therapy. This approach holds great promises for enhancing patient prognosis and leading a new revolution in breast cancer treatment.